(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Esomeprazole is a proton-pump inhibitor and was used in the treatment of gastric acid disorders. Esomeprazole oral thin films are fast dissolving films and are a new, patient-friendly, and more convenient formulation of esomeprazole, which can be taken with or without water. It disintegrates rapidly in the mouth and is swallowed easily with the patient’s saliva. This is an improved alternative formulation for all patients and offers the benefit of an alternative choice of administration of esomeprazole. This article deals with the formulation and evaluation of esomeprazole oral thin films (OTFs). The main objective of this study was to study the effect of combination of synthetic polymer [Hydroxypropyl methyl cellulose (HPMC15CPS)] and natural polymers (carrageenan / pectin / Maltodextrin) on the film forming properties and dissolution rate of the drug. The films were prepared by solvent casting method, using natural and synthetic film forming polymers in different concentrations; PEG 400 is used as plasticizer, aspartame and vanilla flavor as artificial sweetener and artificial flavor respectively. The prepared films were evaluated for weight uniformity, film thickness, folding endurance, dispersion test, drug content, and in vitro dissolution studies to ensure the physical stability of films. The formulation F12 with (HPMC15CPS: carrageenan: pectin in the ratio of 2:1:1 respectively) has physicochemical, mechanical properties. F12 films exhibits lower values a t50, t90 of less than 2 min and 10 min respectively, and highest dissolution efficiency at 10 min (DE10) of 66.76%. It follows a first order drug release profile of with regression coefficient (r2) of 0.996 and a first order rate constant (K1) of 0.249 min-1. F12 is considered as optimized formulation with desired properties. Hence the combination of synthetic polymer (HPMC15CPS) and natural polymers (carrageenan and pectin) in the ratio of (HPMC15CPS: carrageenan: pectin: 2: 1: 1) had a significant effect on the film forming properties and dissolution rate of the drug. The optimized formulation (F12) passes the accelerated stability studies as per ICH guidelines. Fast dissolving esomeprazole oral thin films are suitable for effective and well-tolerated treatment option in the management of gastric acid-related disorders.